2006
DOI: 10.1161/circulationaha.105.610303
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes With Atrial-Based Pacing Compared With Ventricular Pacing

Abstract: Background-Several randomized trials have compared atrial-based (dual-chamber or atrial) pacing with ventricular pacing in patients with bradycardia. No trial has shown a mortality reduction, and only 1 small trial suggested a reduction in stroke. The goal of this review was to determine whether atrial-based pacing prevents major cardiovascular events. Methods and Results-A systematic review was performed of publications since 1980. For inclusion, trials had to compare an atrial-based with a ventricular-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(118 citation statements)
references
References 33 publications
4
103
0
11
Order By: Relevance
“…The evidence is stronger for patients with sinus node disease, in whom dual-chamber pacing confers a modest reduction in AF and stroke, but not in hospitalization for HF or death compared with ventricular pacing. In patients with acquired atrioventricular block, large randomized parallel trials were unable to demonstrate the superiority of dual-chamber pacing over ventricular pacing with regard to hard clinical endpoints of mortality and morbidity [4,[6][7][8]. The benefit of dualchamber over ventricular pacing is primarily due to the avoidance of pacemaker syndrome and to improved exercise capacity [14].…”
Section: Bradycardia Mode and Rate Programmingmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence is stronger for patients with sinus node disease, in whom dual-chamber pacing confers a modest reduction in AF and stroke, but not in hospitalization for HF or death compared with ventricular pacing. In patients with acquired atrioventricular block, large randomized parallel trials were unable to demonstrate the superiority of dual-chamber pacing over ventricular pacing with regard to hard clinical endpoints of mortality and morbidity [4,[6][7][8]. The benefit of dualchamber over ventricular pacing is primarily due to the avoidance of pacemaker syndrome and to improved exercise capacity [14].…”
Section: Bradycardia Mode and Rate Programmingmentioning
confidence: 99%
“…The results of a number of large-scale, prospective randomized trials demonstrated a significant reduction in AF in pacemaker patients with atrial-based pacing (AAI or DDD) compared with patients with ventricular-based pacing [4,8,29]. In the Mode Selection Trial, which enrolled 2010 patients with sick sinus syndrome, the risk of AF increased linearly with the increasing percentage of RV pacing [30].…”
Section: Right Ventricular Pacingmentioning
confidence: 99%
See 1 more Smart Citation
“…С другой стороны, не у всех пациентов, подвергающихся длитель-ной правожелудочковой стимуляции, выявлено увеличе-ние смертности или развитие ХСН [8].…”
Section: кардиология и сердечно-сосудистая хирургия 1 2015unclassified
“…Enfermedad del nodo sinusal (recomendaciones [1][2][3] En general, la BS es una indicación para la estimulación cardiaca solo si la bradicardia es sintomática. Los síntomas podrían estar presentes en reposo, pero con más frecuencia aparecen durante el ejercicio.…”
Section: Indicaciones Para La Estimulación Cardiacaunclassified